2015
DOI: 10.1016/j.infsof.2014.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Validating a model-driven software architecture evaluation and improvement method: A family of experiments

Abstract: ElsevierGonzález Huerta, J.; Insfrán Pelozo, CE.; Abrahao Gonzales, SM.; Scanniello, G. (2015 Context: Software architectures should be evaluated during the early stages of software development in order to verify whether the Non-Functional Requirements (NFRs) of the product can be fulfilled. This activity is even more crucial in Software Product Line (SPL) development, since it is also necessary to identify whether the NFRs of a particular product can be achieved by exercising the variation mechanisms provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
18

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 59 publications
0
11
0
18
Order By: Relevance
“…In the last few years, several methods for evaluating software architectures have been defined: scenario-based (SAAM, architecture tradeoff analysis method (ATAM), ALMA , etc.) [ 40 , 41 , 42 , 43 , 44 , 45 ], mathematical model-based (reliability analysis, performance analysis) [ 46 ] and metrics-based software architecture evaluation methods (QuADAI ) [ 47 ]. In order to evaluate the advantages of the proposed architecture, based on the previously-mentioned methods, a simplified approach of the architecture tradeoff analysis method (ATAM) has been selected to perform a comparative analysis [ 40 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the last few years, several methods for evaluating software architectures have been defined: scenario-based (SAAM, architecture tradeoff analysis method (ATAM), ALMA , etc.) [ 40 , 41 , 42 , 43 , 44 , 45 ], mathematical model-based (reliability analysis, performance analysis) [ 46 ] and metrics-based software architecture evaluation methods (QuADAI ) [ 47 ]. In order to evaluate the advantages of the proposed architecture, based on the previously-mentioned methods, a simplified approach of the architecture tradeoff analysis method (ATAM) has been selected to perform a comparative analysis [ 40 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…[40][41][42][43], mathematical model-based (Reliability Analysis, Performance Analysis) [44] and metrics-based software architecture evaluation methods (QuADAI) [45]. In order to evaluate the advantages of the proposed architecture, based on previously mentioned methods, a simplified approach of Architecture Tradeoff Analysis Method (ATAM) method has been selected to perform a comparative analysis [40,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the results of the systematic review two studies realized experimental evaluations in evaluation of architecture of software product line Gonzalez-Huerta et al (2015) and for a UML-based approach to modeling variabilities, such as SMarty and PLUS (Reinhartz-Berger and Sturm, 2014). Gonzalez-Huerta et al (2015), after an analysis of literature identified a low number of empirical validations of evaluation methods for software architectures.…”
Section: Threats To External Validitymentioning
confidence: 99%
“…Gonzalez-Huerta et al (2015), after an analysis of literature identified a low number of empirical validations of evaluation methods for software architectures. Such a low number of empirical studies, quantitative and qualitative comparisons with existing methods has been neglected and the low number of studies replications.…”
Section: Threats To External Validitymentioning
confidence: 99%
See 1 more Smart Citation